An approach to market biofuel from waste castor bean shell - Azyyati, Johari (2012)
The objectives of this study are to utilize the waste of castor bean shell as biofuel source, to investigate market demand of biofuel, and to perform economic analysis on production of biofuel. The main concerns in this study are to reduce the carbon emission which contributes to the Green House Effect, to solve the problems of depletion of fossil fuel because biofuel can be used as gasoline additive and as replacement for gasoline itself. Besides, this study can solve the waste shell problem and prevent the environmental pollution. This approach is an alternative way to avoid from using food crops as feedstock such as corn, sugar baggasse because we want to control the food price in the future. Thus, producing bioethanol using non edible source is seen as a good fuel alternative because the source crops can be grown renewably and in most climates around the world especially in Malaysia. Economic analysis has been performed in this study where the projected bioethanol price has been calculated and the result shows that by using waste castor been shell as raw material, the estimated price of bioethanol is RM 2.04/liter. In order to lowering the selling price of bioethanol, blending with gasoline is preferred. Overall, this feasibility study shows that the plant will be a profitable plant and it is considered to be a very promising industrial opportunity. Thus, biofuel is highly renewable resources and has highly potential to be penetrated in the market area.